2016
DOI: 10.1007/s11239-016-1435-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of risk factors for inappropriate and suboptimal initiation of direct oral anticoagulants

Abstract: Direct Oral Anticoagulants (DOACs) require specific dosing and monitoring to ensure safe and appropriate use. The purpose of this evaluation was to identify patient- and process-related factors that correlate with increased risk of inappropriate prescribing of DOACs. A retrospective chart review was conducted in three outpatient clinics within an academic medical center to identify patients started on DOAC therapy and evaluate the appropriateness of DOAC initiation. Data collected included patient demographics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 19 publications
8
34
0
Order By: Relevance
“…Inappropriate dosing rates in AF patients varied from 7.7 to 42.0% for dabigatran, from 13.0 to 29.8% for rivaroxaban, and from 12.7 to 48.1% for apixaban. Other studies, including a mix of AF and VTE patients, such as the present study, showed similar results (Armbruster et al, 2014 ; Larock et al, 2014 ; Pattullo et al, 2016 ; Howard et al, 2017 ; Whitworth et al, 2017 ). Dosing appropriateness in these studies was evaluated based on the SmPC or the medication appropriateness tool (MAI).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Inappropriate dosing rates in AF patients varied from 7.7 to 42.0% for dabigatran, from 13.0 to 29.8% for rivaroxaban, and from 12.7 to 48.1% for apixaban. Other studies, including a mix of AF and VTE patients, such as the present study, showed similar results (Armbruster et al, 2014 ; Larock et al, 2014 ; Pattullo et al, 2016 ; Howard et al, 2017 ; Whitworth et al, 2017 ). Dosing appropriateness in these studies was evaluated based on the SmPC or the medication appropriateness tool (MAI).…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have reported a poor adherence rate with dosing guidelines for the DOACs regardless of the renal function. These data suggest that inappropriate DOAC dosing is common and varies from 12.8 to 34.0% of adult hospitalized AF patients as well as other patients taking a DOAC (Armbruster et al, 2014 ; Larock et al, 2014 ; Kucey et al, 2016 ; Pattullo et al, 2016 ; Steinberg et al, 2016 ; Basaran et al, 2017 ; Howard et al, 2017 ; Shrestha et al, 2017 ; Whitworth et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Even if the NOACs are marketed as having simplified dosing as compared with that for warfarin, the appropriate dose of these agents is dependent on several patient-specific factors, such as age, weight, baseline renal and hepatic impairment and concomitant drug use [16]. As shown in a previous study, in which the majority of patients on an inappropriate dose of OAC were found to be on a lower dose than recommended [25], we also found that most errors were due to unnecessarily reduced doses. This is probably due to the fact that it has been shown that lower doses are associated with a reduction in the risk of major bleeding [26].…”
Section: (Continues)mentioning
confidence: 99%
“…No dose adjustment information is provided for dabigatran in regard to hepatic impairment . One small study of 167 patients receiving DOACs found that hepatic function tests were most frequently omitted from monitoring, relative to serum creatinine and hemoglobin . Thus poor consistency with regard to laboratory monitoring may represent an unmet need that can be fulfilled by ongoing DOAC monitoring.…”
Section: Challenges and Opportunities In Doac Managementmentioning
confidence: 99%